الأخطاء اللغوية الكتابية لدى الطلاب الملايويين فى استخدام المصدر : دراسة تحليلية - حانيزم محمد غزالى (al-Jami'ah al-Islamiyah al-'Alamiyah bi-Maliziya, 2004)
This study attempts to identify the actual problems that Malay students face when they use various types of Arabic verbal nouns in their writing. It also aims to find out the frequency of the types of errors in the use of Arabic verbal nouns based on the statistical analysis presented in this study. The study adopts descriptive and analytical methods to analyse the errors occurred in students’ writings, enumerate the percentages of errors and assign the sources of errors. The sample selected for this study consisted of 200 Malay students who specialized in Arabic and from students in Islamic Revealed Knowledge who took the writing skill course as an elective subject to complete their studies during the academic year of 2003 / 2004. The study reveals that the learners’ errors amounted to 1070. The rank order of the types of errors is as follows: substitution and misplacement (81.33 %); omission (9.15 %); selection (5.79